Keanekaragaman Vegetasi Tumbuhan Gymnospermae Di Komplek Vetpur Medan Estate - Ratna Dewi Munthe; Tamara .; Annisa Aulia Nanda; Indayana Febriani Tanjung (Fakultas Matematika & Ilmu Pengetahuan Alam - Universitas Islam Malang, 2023)
The researchers believe that an inventory of gymnosperm plants is necessary to determine the diversity of gymnosperms present in the Vetpur complex. The purpose of this research is to find out information on plants that are scattered in the complex area for further study and as a source of information for researchers and the public in studying plants and their uses. Especially in the classification, research and utilization of these plants. This research was conducted in the Vetpur complex area of Medan using research/direct observation methods on land with grassland ecosystems, observing the diversity of plant seeds that grow around the land. Any seed plants found were recorded and then tested. Identification of plants is carried out by observing the morphological characters of plants which include the characteristics of each class and family and genus in the Phanerogamae plant classification. Contains leaves, stems and flowers and fruits. Then we gather information to create family descriptions. Based on research results obtained from observations, there are 5 types of Gymnospermae plants namely Casuarina equisetifolia, Gnetum gnemon, Lemon cypress, Thuja orientalis, and Cycas rumphii.